Influencing Factors of Urban Residents’ Green Consumption Behaviour in Henan Province, China - Guo, Jing (Scholar: Human Sciences, 2024)
Purpose: Green consumption has gained widely attention in China due to the pressure on scared resources and environment concern is constantly increasing. This study explores the factors that affect the green consumption of urban residents in Henan, China. Based on the theories of Theory of Consumption Value (TCV), Theory of Related Action (TRA), and Theory of Planned Behavior (TPB), the research framework was constructed, which consisted of six independent variables, which are environmental concern, attitude, subjective norm, expectancy, perception and intention. A dependent variable is behavior. Research design, data, and methodology: The study selected urban residents aged 18-59 from five cities in Henan Province as the main target population. The researcher collected the data by distributing online questionnaire to 483 consumers and analyzed the data using confirmatory factor analysis and structural equation model. Results: The results approve all hypotheses. Environmental concerns significantly influence green consumption attitudes. Attitude, subjective norm, expectancy, and perception significant influence the intention of green consumption. Additionally, Environmental concerns and intention significantly influence behavior. Conclusions: The obtained data may need to be more widely promoted and applied in China. However, the relevant data can provide an overall understanding of the influencing factors of Chinese consumers’ green consumption behavior.